Development and psychometric validation of the digital socialization scale - Khubaib Khalid; Noman Aftab; Maaz Ahmed; Zeba Khan; Maria Muzaffar Janjua (Cogent Psychology)
Digital socialization, is a process by which individuals, particularly adolescents, acquire skills, norms, and behaviors through digital interactions, has become increasingly significant in the context of modern social dynamics. The scale in the current study was developed through a rigorous methodological process, including item pool generation, expert reviews, and both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The final scale consisted of 32 items distributed across seven factors: Social Influence and Peer Pressure, Media Literacy and Critical Thinking, Digital Citizenship and Ethics, Emotional Regulation and Empathy, Global Connectivity and Cultural Exchange, and Religious and Spiritual Exploration. The scale demonstrated strong internal consistency with a Cronbach’s alpha of .77 and high construct validity, as evidenced by significant factor loadings and fit indices. The Digital Socialization Scale offers valuable insights for researchers, educators, and clinicians to assess and promote healthy digital interactions among adolescents. Future research should focus on cross-cultural validation and periodic updates to align with evolving digital trends.